Penerapan Instrumen pada Anak Berkebutuhan Khusus dalam Katagori Bahasa/ Komunikasi di MI Nurul Falah III Kabupaten Tangerang (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study focuses on describing the communication conditions and language barriers experienced by Children with Special Needs (CSN) in the language/communication category at MI Nurul Falah III, Tangerang Regency. In addition, the research examines the use of instruments applied to support the improvement of students’ abilities. A descriptive qualitative approach was employed through observation and interviews with two students in grades V and VI who exhibited symptoms of aphasia and speech fluency disorders. The findings indicate that both students were able to understand basic instructions but continued to face challenges in fluent speech, appropriate vocabulary selection, comprehension of abstract concepts, and reading comprehension. Interventions provided included speech therapy with a multisensory approach, the use of concrete media, gradual learning, and strategies to enhance focus and concentration. Overall, this study emphasizes that the appropriate selection of language therapy instruments is crucial to supporting the development of communication skills among CSN in inclusive educational settings.